A Social Strategy How We Profit from Social Media - MikoÅ‚aj Ja n Piskorski (Princeton University Press, 2014)
LinkedInâ€™s road to success was not straightforward. Indeed, in the summer of 2005, Reid Hoffman found himself facing a critical decision regarding the companyâ€™s future. By then, the company had amassed five million users, but it had very little revenue to show to investors. Furthermore, it had only five million dollars in cash reserves, which would allow it to survive for just another nine months without an infusion of cash from venture capitalists. Given about a six-month lead required to obtain financing, LinkedIn had to start generating revenue quickly, or the terms of financing would be very unfavorable. In deciding how to generate revenue, Hoffman had to make sure that he did not undermine the basic principles that had allowed the company to attract users. For example, LinkedIn had always encouraged users to form online connections only with people they actually knew offline. It also allowed members to contact only those members who were no more than four degrees of separation, and every time someone wanted to contact someone else on the platform, the chain of friends connecting the sender and the receiver had to approve the communication. This fostered a trustworthy online environment and reduced the incidence of spam, which helped LinkedIn prevail over competitors. The company also had to be mindful about its superusersâ€”individuals who were so committed to the site that they used a separate computer dedicated only to their LinkedIn activities. Often referred to as â€œnetworkers,â€ these users had established many online relationships on LinkedIn and played critical roles in connecting other users by forwarding their requests. LinkedInâ€™s example shows us that when a firm provides a valuable social solution, it can ask the beneficiaries to do something that benefits the firm in return. In LinkedInâ€™s case, this amounted to paying the firm money. This insight will be particularly useful in the second part of the book when we study more traditional companies, such as Nike or American Express. These companies have built their own social solutions or leveraged existing ones to help their customers interact with others. In return, these firms ask that these customers do something beneficial for the firm, such as buying more expensive products or doing customer acquisition on the firmâ€™s behalf. I will use the concept of social strategy to capture the idea that firms can lower their costs and/or increase their customersâ€™ willingness to pay by helping their customers develop better relationships. Social failures, social solutions, and social strategy are the essential concepts on which this book is based. Chapter 1 explains how the book will explore and use these concepts to understand why certain social platforms have failed while others have succeeded, and how the surviving social platforms compete with each other.